Selective Targeting of a Novel Epsin–VEGFR2 Interaction Promotes VEGF-Mediated Angiogenesis. Issue 6 (18th March 2016) - Rahman, H.N. Ashiqur; Wu, Hao; Dong, Yunzhou; Pasula, Satish; Wen, Aiyun; Sun, Ye; Brophy, Megan L.; Tessneer, Kandice L.; Cai, Xiaofeng; McManus, John; Chang, Baojun; Kwak, Sukyoung; et al.
Abstract : Rationale : We previously reported that vascular endothelial growth factor (VEGF)-induced binding of VEGF receptor 2 (VEGFR2) to epsins 1 and 2 triggers VEGFR2 degradation and attenuates VEGF signaling. The epsin ubiquitin interacting motif (UIM) was shown to be required for the interaction with VEGFR2. However, the molecular determinants that govern how epsin specifically interacts with and regulates VEGFR2 were unknown. Objective : The goals for the present study were as follows: (1) to identify critical molecular determinants that drive the specificity of the epsin and VEGFR2 interaction and (2) to ascertain whether such determinants were critical for physiological angiogenesis in vivo. Methods and Results : Structural modeling uncovered 2 novel binding surfaces within VEGFR2 that mediate specific interactions with epsin UIM. Three glutamic acid residues in epsin UIM were found to interact with residues in VEGFR2. Furthermore, we found that the VEGF-induced VEGFR2–epsin interaction promoted casitas B-lineage lymphoma–mediated ubiquitination of epsin, and uncovered a previously unappreciated ubiquitin-binding surface within VEGFR2. Mutational analysis revealed that the VEGFR2–epsin interaction is supported by VEGFR2 interacting specifically with the UIM and with ubiquitinated epsin. An epsin UIM peptide, but not a mutant UIM peptide, potentiated endothelial cell proliferation, migration and angiogenic properties in vitro, increased postnatal retinal angiogenesis, and enhanced VEGF-induced physiological angiogenesis and wound healing. Conclusions : Distinct residues in the epsin UIM and VEGFR2 mediate specific interactions between epsin and VEGFR2, in addition to UIM recognition of ubiquitin moieties on VEGFR2. These novel interactions are critical for pathophysiological angiogenesis, suggesting that these sites could be selectively targeted by therapeutics to modulate angiogenesis. Abstract : Supplemental Digital Content is available in the text.